Tafsir in its Context, or How Socio-Political Milieu Informed What to Include and Exclude in Qur’an Commentaries: At-Tabari’s, Ibn Abi Hatim’s, and al-Maturidi’s Interpretations of Surah Al-Ma’idah (5): 51 as a Case Study - Muchlisin, Annas Rolli (Lajnah Pentashihan Mushaf Al-Qur'an, 2024)
This paper analyzes the interpretations of Qur’an surah al-Ma’idah (5): 51 by three 10th-century exegetes: at-Tabariy, Ibn Abi Hatim, and al-Maturidiy. It argues that at-Tabariy’s commentary, though foundational, represents just one model of exegesis in the medieval period. Ibn Abi Hatim and al-Maturidiy incorporate unique interpretative materials, not found in at-Tabariy’s work. Al-Maturidiy offers three types of interpretation, while Ibn Abi Hatim narrates a story about Caliph ‘Umar’s anger at a companion hiring a Christian secretary. The study also contextualizes these interpretations within the socio-political environment of the 10th-century ‘Abbasid era, where non-Muslims gained influence. This article concludes that the Qur’an commentators’ decision to include and exclude certain interpretative materials in their tafsir works reflects, to some degree, the socio-political environments in which they lived and authored their works. Qur’an commentaries, like any other book, were not written in a vacuum.